Tư tưởng Hồ Chí Minh về vấn đề nông dân - Nguyễn, Khánh Bật (2011)
Tác giả: Nguyễn Khánh Bật, TS; Phạm Ngọc Anh; Phạm Văn Bính; Vũ Văn Châu; Phạm Hồng Chương; Nguyễn Thị Kim Dung; Nguyễn Bích Hạnh; Trần Hải; Phan Minh Hiền; Nguyễn Bá Linh; Nguyễn Huy oánh; Bùi Đình Phong; Lê Ngọc Tòng; Hoàng Trang; Nguyễn Tứ -- Từ khóa: Tư tưởng Hồ Chí Minh; Nông dân